EI as an emergent technique for healthcare workers: A comprehensive literature review and future research agenda - Rani, Priya; Sherry (Journal of Social Review and Development, 2025)
Purpose – The study aims to systematically review the role and significance of emotional intelligence (EI) among healthcare professionals (HCPs), with a focus on its impact on stress management, resilience, empathy, and professional performance in both pandemic and general healthcare settings. Design/methodology/approach – A systematic literature review and scientometric analysis were conducted using the SCOPUS database. A total of 146 articles were initially retrieved, and after applying inclusion–exclusion criteria, 42 relevant publications from 2015 to 2024 were analysed. Manual screening and analysis were performed using R-Studio and MS Excel. Findings – The results indicate a growing trend of research on EI among HCPs, particularly after the COVID-19 pandemic. Frequently used keywords included “emotional,” “intelligence,” “healthcare,” and “workers,” alongside emerging terms such as “resilience” and “emotional distancing.” The most prominent journals in this field are Frontiers in Psychology and Healthcare (Switzerland). The review highlights EI as a predictor of organizational adaptability and identifies its critical role in mitigating burnout, enhancing empathy, and improving patient–provider relationships. Research limitations/implications – The study is limited to the SCOPUS database and English-language publications, which may affect the comprehensiveness of coverage. Future research should incorporate broader databases, multilingual sources, and cross-cultural perspectives to capture a wider scope of EI studies. Practical implications – The findings suggest the integration of EI-based training and assessment in healthcare systems to strengthen stress tolerance, resilience, and professional well-being. EI should also be considered in recruitment and professional development processes. Social implications – By addressing burnout and promoting empathy, EI contributes to improved patient care, enhanced patient satisfaction, and stronger healthcare outcomes, while also highlighting the need for greater societal recognition of emotional competence. Originality/value – This study provides one of the few systematic and scientometric reviews of EI among healthcare workers, offering a comprehensive overview of research trends, knowledge gaps, and practical strategies. It contributes to theory-building while providing actionable insights for healthcare practitioners, policymakers, and future researchers.